PENGARUH EKSTRAK ETANOLIK 50% HERBA PEGAGAN (Centella asiatica (L.) Urban) TERHADAP PENINGKATAN PROLIFERASI SEL LIMFOSIT MENCIT JANTAN GALUR Balb/c YANG DIINDUKSI VAKSIN HEPATITIS B - Nikmah Nur Khusnawati; Suwijiyo Pramono; Ediati Sasmito (Majalah Obat Tradisional, 2015)
Pegagan (Centella asiatica (L.) Urban) has been known as multi effect plant that empirically used in the traditional medicine. This research aims to evaluate the effect of 50%ethanolic extract of pegagan herb against increased lymphocyte proliferation cells in Balb/c mice that induced with hepatitis B vaccine, and also to evaluate triterpen glicosida compound (asiaticosida) of 50% ethanolic extract of pegagan herb. The test was done by 60 Balb/c male mices that divided into 6 groups : control group, testing group that was treated with pegagan extract dose of 25 mg/KgBB, 50 mg/KgBB, 100 mg/KgBB, 200 mg/KgBB and 400 mg/KgBB. All of mices were vaccinated on day 0 and days 15. Furthermore, identification of triterpen glicosida compound was done by KLT method using BAW 4:1:5 as upper eluen. Lymphocyte cells were isolated and the cells proliferation measured by MTT reduction method. Data was analyzed statistically using 95% confidence level. The result shown that 50% of ethanolic extract of pegagan herb did not give  the immuomodulatory effect while the identification test shown that 50% of extract of pegagan herb has triterpen glicosida compound (asiaticoside).